2020
DOI: 10.1080/1360080x.2020.1737343
|View full text |Cite
|
Sign up to set email alerts
|

Can grants affect student performance? Evidence from five Italian universities

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Using a sample of students enrolled in US public universities, the author found that the students who receive financial aid are more likely to graduate in the year they turn 24 than those who do not receive loans. Finally, a recent study carried out by Graziosi et al (2020) with a sample of Italian university students also showed a positive effect of receiving grant financial aid on the likelihood of graduating, achieving a higher number of credits, and avoiding dropout.…”
Section: Financial Independence As Key Element For the Development Ofmentioning
confidence: 84%
“…Using a sample of students enrolled in US public universities, the author found that the students who receive financial aid are more likely to graduate in the year they turn 24 than those who do not receive loans. Finally, a recent study carried out by Graziosi et al (2020) with a sample of Italian university students also showed a positive effect of receiving grant financial aid on the likelihood of graduating, achieving a higher number of credits, and avoiding dropout.…”
Section: Financial Independence As Key Element For the Development Ofmentioning
confidence: 84%
“…Fuente: elaboración propia Entre las relaciones positivas entre becas y rendimiento, Graziosi et al (2020) constatan que, entre 7.415 estudiantes de primer año matriculados en cinco universidades italianas, las subvenciones basadas en la necesidad tienen un impacto positivo y significativo en el éxito estudiantil, contribuyendo a completar los estudios, graduarse y disminuir probabilidad de abandono en primer año, principalmente en disciplinas de humanidades y ciencias sociales.…”
Section: Gráfico 3 Categorización De Artículos Según Enfoque Principalunclassified
“…In a study by Graziosi et al (2020), conducted with university students (Italy), it was revealed that the strategy of seeking grant support is becoming popular among the student environment, that receiving financial assistance in the form of a grant has a positive impact on the student budget [18].…”
Section: O V Kotomina Believes That Interest In the Problems Of Thementioning
confidence: 99%